2010
DOI: 10.2172/1002088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chloride content of molten nitrate salt on corrosion of A516 carbon steel.

Abstract: The corrosion behavior of A516 carbon steel was evaluated to determine the effect of the dissolved chloride content in molten binary Solar Salt. Corrosion tests were conducted in a molten salt consisting of a 60-40 weight ratio of NaNO 3 and KNO 3 at 400°C and 450°C for up to 800 hours. Chloride concentrations of 0, 0.5 and 1.0 wt.% were investigated to determine the effect on corrosion of this impurity, which can be present in comparable amounts in commercial grades of the constituent salts. Corrosion rates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…These results are in agreement with previous studies of corrosion tests reported by Bradshaw et al. [19].…”
Section: 1compositional and Morphological Analysissupporting
confidence: 94%
“…These results are in agreement with previous studies of corrosion tests reported by Bradshaw et al. [19].…”
Section: 1compositional and Morphological Analysissupporting
confidence: 94%
“…Commercial salts of different sources may contain various levels of impurities such as carbonates, chlorides, and sulfides. Among these impurities, chlorides can significantly increase the corrosivity of the salts . The influence of chloride impurities on the corrosion behavior of solar salt containment materials has only been studied in very few cases and the mechanism is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors reported interesting results about the influence of chloride content in the corrosion performance of carbon steel showing a dependency between corrosion rates and chlorides content [21][22][23][24]. However, these results are associated to short corrosion tests which would be insufficient for a detailed evaluation of corrosion mechanism or longer thermalcorrosive treatments analyzing the effect of chloride content up to 1% by weight.…”
Section: Introductionmentioning
confidence: 99%